Research methodology in women's studies - Shukla,Asha (Serials publications PVT ltd, 2017)
This book presents a fairly comprehensive understanding of the concept of Women's Studies and methodology by the discipline in the course of its evolution. Adoption of appropriate methodology is an essential characteristic of quality research. The present book provides the basic tenets of methodological research so that researchers may become familiar with the art of using research methods and techniques. This book will be of immense use for students of graduate, M Phil and also Ph D level. The book is, in fact, an outgrowth of experience of research and teaching the subject.